Iodine status, psychomotor and cognitive functions of children in an urban poor community - Amarra, Ma. Sofia V. (2001)
The study examined the extent to which various dietary, biochemical, anthropometric, health and environmental factors contributed to the variance in iodine status of schoolchildren in an urban poor community, and compared that psychomotor and cognitive functions of iodine deficient and non-iodine deficient children. The presence of iodine deficiency was assessed by means of goiter palpation and urinary iodine excretion (UIE) from spot casual urine samples. Psychomotor and cognitive functions were tested using Raven's Colored Progressive Matrices and Bender-Gestalt test. Two groups of children, ages ranging from 6 to 10 years, were selected on the basis of normal and deficient iodine status. Children with normal iodine status (n=38) had UIE greater than or equal to 100 ug/L and no goiter palpated; children with deficient iodine status (n=39) had UIE less than 100 ug/L and had either grade one or grade 0 goiter. The two groups were examined for differences in dietary intake, hemoglobin level, serum retinol level, whole blood selenium, anthropometric measurements, parasitic infection, access to potable drinking water, use of iodized salt, and presence of illness in the past two weeks. Dietary, biochemical, anthropometric, health and environmental factors contributed 57 percent to the variability in schoolchildren's iodine status (p < 0.5) The use of coffee and dietary intake of riboflavin gave the most significant contributions to the variance in children's iodine status. Children who did not drink coffee and whose riboflavin intake met at least 80 percent of requirements were most likely to have normal iodine status. Dietary quality, expressed as percentage of total energy intake from the various food groups, differed between groups. Children with normal iodine status consumed significantly greater proportions of fresh pork and beef, milk and milk products, and a fortified chocolate beverage compared to iodine-deficient children. Anemia, Vitamin A deficiency, and low blood selenium levels were prevalent ion both groups. Stunting but not wasting was high in both groups. Majority of thee households did not have potable drinking water and did not use iodized salt. Prevalence of illness was low and parasitism appeared to be high regardless of iodine status. There were no significant differences in psychomotor and cognitive function scores between iodine-deficient and non-deficient children. However, classes with better indicators of iodine status also showed significantly higher levels of general ability among those children tested. Additional analysis showed that iodine status and the use of iodized salt significantly predicted the level of mental performance. The failure to find a relationship between individual test scores and iodine status was most likely due to the presence of other micronutrient deficiencies which blunt the response to iodine intake, protein calorie malnutrition, and the use of an inadequate sample size.